Writing write-downs: the rhetoric of goodwill impairment. Issue 1 (18th April 2017) - Sandell, Niklas; Svensson, Peter
Abstract : Purpose: The aim of this paper is to study the rhetoric of goodwill impairment, more specifically rhetoric, as it is constructed in the form of accounts (i.e. statements that explain unanticipated or untoward behavior). The authors argue that goodwill impairment is not only a technical matter but also a rhetorical practice by means of which external scrutiny is responded to. Design/methodology/approach: The data corpus consists of explanations provided by corporations regarding impairment of goodwill. Data were collected from annual reports from companies quoted on NASDAQ OMX Stockholm, Sweden. The impairment explanations were analyzed according to a taxonomy of account types. The explanations were subjected to close reading to discern the potential rhetorical functions of the different accounts. Findings: Seven account types are identified and discussed, namely, excuse, justification, refocusing, concession, mystification, silence and wordification. Research limitations/implications: There is a need for further research that explores the process of authorship (i.e. writing, editing, negotiating and revising) through which the texts of financial communication are produced. Practical implications: The findings have implications for the future formulations of standards regarding qualitative explanations in financial reporting in general and explanations of goodwill impairment in particular. Originality/value: The paper contributes to the knowledge about the use of natural language and rhetoric in financial communication.